STRATEGI DAKWAH SYEKH JALALUDDIN, MURID SUNAN BONANG DI PESANTREN CANGAAN BANGIL - Khoirul Anam; Wachyuni (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
Indonesian Islam has its own strategy in conveying the mission of preaching the successor to the message of Allah's messenger. The strategy is very varied so that the results of the achievement are quite successful and survive and even grow. Several ways of Islamization in Indonesia are through politics, marital relations, trade, arts, tasawwuf, and no less important is through education. Islamic boarding schools are also indirectly the development of Islamic da'wah. Because what is brought in the Islamic mission is found in Islamic boarding schools, Islamic Shari'a and the teachings of Sufism. In addition, the advantages of Islamic da'wah through education, which in this case is pesantren, is a chain of teachers who continue to be continued with other teachers until they meet with the Messenger of Allah. So here it is certain to find a meeting point from whom the chain of da'wah through education is connected. A relationship that is not simple, it can be said that a very strong and solid inner relationship is the line of preachers of Kyai and santri. This study uses a qualitative method, while the method of data collection is by conducting observation and interviews with several caregivers of the Cangaan Islamic boarding school as well as alumni or teachers. As a student of Sunan Bonang who has a mandate to carry out da'wah, Syekh Jalaluddin must have looked first at the condition of the surrounding community. Syekh Jalaluddin has a strategy for the Gempeng Bangil community and its surroundings, namely through the introduction of theology. An educational intermediary that is built as a wasilah for the delivery of da'wah is the right choice for the residents of Gempeng and its surroundings. The theological messages conveyed by Sheikh Jalaluddin as the key to da'wah are literature that is connected to Sunan Bonang as his teacher.